Probiotics and prebiotics in clinical tests: an update - Brüssow, Harald (F1000Res, 2019)
Probiotics have been explored in an exponentially increasing number of clinical trials for their health effects. Drawing conclusions from the published literature for the medical practitioner is difficult since rarely more than two clinical trials were conducted with the same probiotic strain against the same medical condition. Consequently, the European Society for Paediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN) made a few recommendations restricting it to probiotic use against acute gastroenteritis and antibiotic-associated diarrhea. Recent studies also made a strong case for probiotic use against sepsis in preterm and term infants from developing countries. Conclusions on the value of probiotics are best based on detailed meta-analyses (MA) of randomized controlled trials (RCT). Outcomes of MA are discussed in the present review for a number of gastroenterology conditions. Since these MA pool data from trials using different probiotic species, large RCT published sometimes come to different conclusions than MA including these studies. This is not necessarily a contradiction but may only mean that the specific probiotic species did not work under the specified conditions. Positive or negative generalization about probiotics and prebiotics should be avoided. Credible effects are those confirmed in independent trials with a specified probiotic strain or chemically defined prebiotic in a specified patient population under the specified treatment conditions. Even distinct technological preparations of the same probiotic strain might affect clinical outcomes if they alter bacterial surface structures. Underpowered clinical trials are another problem in the probiotic field. Data obtained with sophisticated omics technologies, but derived from less than ten human subjects should be interpreted with caution even when published in high impact journals.